HOW TO TEACH THE DISPOSSESSED BY LE GUIN? - Gassim DOHAL (Association of Social and Educational Innovation, 2022)
Ursula K. Le Guin proposes two dialectical worlds in a circular pattern and non-linear structure in her novel The Dispossessed. She also manages to mention and critique our earth in her book. And for science fiction teachers, teaching such a novel could be a nightmare. As a result, a lesson plan is created to aid in the teaching of this novel.